The Usefulness of Functional Near-Infrared Spectroscopy for the Assessment of Post-Stroke Depression - Koyanagi, Masahiko; Yamada, Mai; Higashi, Toshio; Mitsunaga, Wataru; Moriuchi, Takefumi; Tsujihata, Mitsuhiro (Frontiers in Human Neuroscience, 2021)
Background: Post-stroke depression (PSD) is the most common mood disorder following stroke and is also the main factor that limits the recovery and rehabilitation of patients with stroke. The prevalence of PSD is ~30%. Since there is no gold standard for the diagnosis and evaluation of PSD, it is important to raise awareness of PSD and to establish methods for its evaluation, early diagnosis, and treatment. In the field of psychiatry, functional near-infrared spectroscopy (fNIRS) has been used as a diagnostic tool for the measurement of oxygenated hemoglobin (oxy-Hb). This study aimed to assess whether fNIRS could be applied in the diagnosis and evaluation of PSD. Methods: We recruited 45 patients with stroke, who were admitted to Nagasaki Kita Hospital between May 2015 and April 2019. The 17-item Hamilton Rating Scale for Depression (HAMD17), which is considered to be a useful screening and evaluation tool for PSD, was used for the assessment of patients after stroke; moreover, oxy-Hb was measured in the pre-frontal cortex. The subjects were divided into two groups: the depressed group (n = 13) and the non-depressed group (n = 32). We evaluated the correlation between the oxy-Hb integral values and HAMD17 scores. Results: We investigated the relationship between the oxy-Hb integral values and HAMD17 total scores, and found a negative correlation between them (ρ = −0.331, P < 0.005). There was a significant difference in the oxy-Hb integral values during the activation task period between the depressed and non-depressed groups (3.16 ± 2.7 and 1.71 ± 2.4, respectively; P = 0.040). The results indicated that the patients of the depressed group showed lower oxy-Hb integral values and lower activation in the frontal lobe in comparison with the patients of the non-depressed group. Conclusion: The present study highlights that the measurement of oxy-Hb by using fNIRS is a useful methodology for the diagnosis of PSD in patients after stroke.